1986
DOI: 10.1111/j.1600-0870.1986.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments on the genesis of vortices over the Qinghai-Tibet plateau

Abstract: The formation of a vortex and shear line over the Qinghai‐Tibet Plateau (QTP) was investigated with numerical experiments using the ECMWF grid point model. The case chosen occurred between 24 and 26 July, 1982, when the south‐west monsoon invaded the QTP and a vortex developed. The correct simulation of the vortex in the model shows that it is possible to predict the atmospheric circulation over the QTP and the consequent weather over China. When the simulation was rerun with a dry model (i.e., without the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…An intensified LLJ, wind speed 15m s-1, is simulated around the south border of the QTP. This result is similar to that obtained in another numerical case study by Dell'Osso and Chen (1986). Also Bannon (1982) found that the slope of the Somali high land is essential in determining the strength of the cross-equatorial eastern Africa LLJ ; the steeper the slope, the stronger the LLJ.…”
Section: Envelope Qtp Experimentssupporting
confidence: 79%
See 1 more Smart Citation
“…An intensified LLJ, wind speed 15m s-1, is simulated around the south border of the QTP. This result is similar to that obtained in another numerical case study by Dell'Osso and Chen (1986). Also Bannon (1982) found that the slope of the Somali high land is essential in determining the strength of the cross-equatorial eastern Africa LLJ ; the steeper the slope, the stronger the LLJ.…”
Section: Envelope Qtp Experimentssupporting
confidence: 79%
“…The horizontal grid length is 1.875* longitude/latitude. This resolution may be too coarse for simulating meso-scale * disturbances, but is appropriate if our aim is to simulate the broad features of the circulation systems rather than its detail (Dell'Osso and Chen, 1986). The integration area is 0*N to 70*N and 40*E to 160*E. The boundary values are updated every time step (15 min) and obtained from a linear interpolation of the analyses taken at 12 h intervals.…”
Section: Description Of the Model And Experimentsmentioning
confidence: 99%
“…More cases for both types of vortices should be selected and numerical experiments should be performed in the future, to gain more credible conclusions on the evolution and movement mechanisms of the plateau vortices. In addition, because the topography can affect the dynamic and thermodynamic processes on the atmosphere over the Tibetan Plateau, and is an important factor affecting the evolution process of the vortices (Dell'Osso and Chen, 1986;Shen et al, 1986a;Wang, 1987), the influence of the topography on the evolution of the plateau vortices should also be investigated through numerical experiments in the future.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…It is pointed out that the sensible heating exerts a major effect on the formation of the vortices, while the condensation latent heat release is most important during their development phase (Lhasa Group for Tibetan Plateau Meteorology Research, 1981;Dell'Osso and Chen, 1986;Shen et al, 1986aShen et al, , 1986bWang, 1987;Li and Zhao, 2002). Ding and Lu (1990) used a five-layer primitive equation model to simulate the eastward movement of a vortex over the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…The genesis and development of TPVs have been fundamentally attributed to the dynamic and thermodynamic effects of the TP (Luo, ; Wu & Chen, ; Zhang & Zhu, ). As for dynamic effects, the high terrain forces the lower tropospheric flow to split into two branches that join downstream in a region of convergence (Dell'Osso & Chen, ). As for thermodynamic effect, surface sensible heating plays an important role in the development of vortices over the TP in summer (Shen et al, ; Shen & Huang, ).…”
Section: Introductionmentioning
confidence: 99%